ANALYSIS OF CUSTOMER INTEREST AND SERVICE QUALITY IN USE OF MOBILE BANKING ON BANK ACEH SYARIAH KCP KEUTAPANG DUA SERVICE FEATURES - Ismuadi, Ismuadi; Shahaqkiki, Shahaqkiki (Jihbiz: Global Journal of Islamic Banking and Finance, 2025)
Banking services continue to provide updates and improvements. One of the technological advances in business applications is the mobile banking system. This study aims to determine the quality of service in mobile banking at BAS KCP Keutapang Dua, how customer interest in using mobile banking at BAS KCP Keutapang Dua, and how mobile banking is superior compared to other banking products. This study uses a qualitative method. The results of this study explain that the quality of service in the Action Bank Aceh application is very helpful for customers in making transactions, there are many features that meet transaction needs so that customers can quickly navigate the mobile banking application and there is sophisticated security such as two-step verification and data encryption to protect customer information besides that The advantages of mobile banking are fast and efficient transactions. The implications of this study can improve the quality of Bank services, Develop Features that are More Relevant to Customer Needs, More Appropriate Marketing Strategies, Support Digitalization and Inclusion of Sharia Finance and Provide Feedback for Sharia Regulations and Standards.AbstrakLayanan perbankan terus memberikan pembaharuan dan penyempurnaan. Salah satu kemajuan teknologi dalam aplikasi bisnis adalah sistem mobile banking. Penelitian ini bertujuan untuk mengetahui kualitas layanan mobile banking di BAS KCP Keutapang Dua, bagaimana minat nasabah menggunakan mobile banking di BAS KCP Keutapang Dua, dan bagaimana keunggulan mobile banking dibandingkan produk perbankan lainnya. Penelitian ini menggunakan metode kualitatif. Hasil penelitian ini menjelaskan bahwa kualitas layanan pada aplikasi Action Bank Aceh sangat membantu nasabah dalam bertransaksi, terdapat banyak fitur yang memenuhi kebutuhan transaksi sehingga nasabah dapat dengan cepat menavigasi aplikasi mobile banking dan terdapat keamanan yang canggih seperti seperti verifikasi dua langkah dan enkripsi data untuk melindungi informasi nasabah selain itu Keunggulan mobile banking adalah transaksi yang cepat dan efisien. Implikasi dari penelitian ini dapat meningkatkan kualitas layanan Bank, Mengembangkan Fitur yang Lebih Relevan dengan Kebutuhan Nasabah, Strategi Pemasaran yang Lebih Tepat, Mendukung Digitalisasi dan Inklusi Keuangan Syariah serta Memberikan Umpan Balik Terhadap Peraturan dan Standar Syariah.